Characterization of materials using non-contact inductive sensor applications - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Khalifa, Othman Omran; Teddy, -; Zulkefly, Ezamurni; Jaafar, Aisyah; Latif, Khairun Nissaa' Abdul; Abidin, Noraini; AbdWahab, SitiNorkhairani; IzwarArfani, NurulSyuhadah (2011)
Transducers and sensors play an important role in instrumentation and measurement. Expectations from noncontact biomedical implants are getting renewed interests among researchers. A novel work is carried by presenting a non-contact technique as an inductive transducer coils. A theoretical analysis of an inductive transducer is given which is followed by a development of non-contact measurement technique to characterize core materials within a frequency of 1 KHz to 20 KHz. Simulation is carried out using PSpice, Excel and MATLAB software tools. The simulation details are presented exploring the effect of materials through non-contact means.